Dayak Ngaju Customary Fines in Pre-Marriage Agreement to Minimize Divorce in The Perspective of Maslahah Mursalah Ramadhan Al-Buthi - Muhammad Aulia Rahman; Roibin Roibin; Nasrulloh Nasrulloh (El-Mashlahah, 2023)
Before the wedding, the prospective husband and wife in the Dayak Ngaju Palangka Raya community made a pre-marriage agreement in the presence of the Damang (Adat figure). One of the core points of the agreement is that there is a fine for whoever causes a divorce in the household. This is unique and different from marriage agreements in general and in Islam. This study aims to analyze Dayak Ngaju customary fines in pre-marriage agreements implemented by the Dayak Ngaju community to minimize divorce. This research is empirical legal research using a case approach. The primary sources of this research are interviews, documentation, observations, and secondary sources in the form of books, as well as the views of scholars who have discussed this issue. Then this problem is analyzed using the theory of Maslahah Mursalah Ramdhan Al-Buthi. The results of this study indicate that according to the perspective of Adat figure regarding customary fines in pre-marriage agreements carried out by the Dayak Ngaju community, it is a good thing, not only to maintain the customs of their ancestors but also to contain far more meaningful values, namely protecting the existence and maintaining commitments in the marriage. From the perspective of Maslahah Mursalah Ramadhan Al-Buthi, these customary fines are not contrary to Islamic law, if they do not exceed the specified corridors, do not conflict with the higher Al-Quran, Sunnah, Qiyas, and Maslahah, and customary fines may be carried out if the four conditions these limits are not violated.